Research on the carrying capacity of production, living and ecological space and its coupling coordination in Duolun County, Inner Mongolia. - A Ruhan; Dongchang Liu (PLoS ONE)
To offer a foundational science for the land spatial planning of Beijing Tianjin sandstorm source area, the remote sensing images of Duolun County in Inner Mongolia from 2000 to 2020 were used to obtain the spatial information of production, living and ecological space(PLES). In order to construct the index system of the carrying capacity of the PLES, 24 indicators were chosen from the perspectives of ecological space, living space, and production space. AHP method, TOPSIS Model with entropy combination weight, coupling coordination model and obstacle degree model are used to analyze the coupling coordination scheduling and obstacle degree of the PLES carrying capacity. The findings exhibited that (1) the distribution area of ecological space and production space decreased, while the living space area increased slightly; (2) The carrying capacity of production space showed a weak growth trend, the carrying capacity of production space, living space and the PLES space showed a weak downward trend; (3) The coupling degree and coupling coordination degree between two spaces show a slow downward trend; (4) The obstacle degree of the carrying capacity of production space and living space has increased, while the carrying capacity of ecological space is decreasing. Livestock carrying capacity is the most important obstacle restricting the carrying capacity of production space. The scale of construction land has the greatest obstacle to the carrying capacity of living space, the degree of desertification has the greatest obstacle to the carrying capacity of ecological space, and soil organic matter has the greatest obstacle to the comprehensive carrying capacity of the PLES.